Biology of Brain Disorders - Andrew Harkin (Frontiers Research Topics, 2018)
Brain disorders, including neurological and neuropsychiatric conditions, represent a challenge for public health systems and society at large. The limited knowledge of their biology hampers the development of diagnostic tools and effective therapeutics. A clear understanding of the mechanisms that underlie the onset and progression of brain disorders is required in order to identify new avenues for therapeutic intervention.Overlapping genetic risk factors across different brain disorders suggest common linkages and pathophysiological mechanisms that underlie brain disorders. Methodological and technological advances are leading to new insights that go beyond traditional hypotheses. Taking account of underlying molecular, cellular and systems biology underlying brain function will play an important role in the classification of brain disorders in future.In this Research Topic, the latest advances in our understanding of biological mechanisms across different brain disorders are presented. The areas covered include developments in neurogenetics, epigenetics, plasticity, glial cell biology, neuroimmune interactions and new technologies associated with the study of brain function. Examples of how understanding of biological mechanisms are translating into research strategies that aim to advance diagnoses and treatment of brain disorders are discussed.